Zooarchaeological Approaches to the Identification of Bone Fat Production in the Archaeological Record - Peres, Tanya M. (Ethnobiology Letters, 2018)
Mammal fat is an important industrial product and ingredient in culinary dishes and medicines the world over, yet evidence for its use is not often identified in the archaeological record. I first give a brief overview of the importance of bone fats to subsistence and industrial economies. I follow this with criteria for identifying these activities archaeologically. This review concludes with why the identification of such activities is important to our understanding of ancient foodways